2015
DOI: 10.2967/jnumed.115.165407
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for the Diagnosis of Residual or Recurrent Nasopharyngeal Carcinoma After Radiotherapy: A Metaanalysis

Abstract: The aim of this work was to assess the overall value of 18 F-FDG PET/ CT in the diagnosis of residual or recurrent nasopharyngeal carcinoma using a metaanalysis. Methods: The literature published between January 1990 and September 2014 was searched in the PubMed, EMBASE, Cochrane Library, EBSCO, VIP, CNKI, and Wanfang databases to identify eligible studies on PET/CT of residual or recurrent lesions. The methodologic quality of the included studies was evaluated using the "quality assessment for studies of diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…Only 4 of these literature were about NPC and they all analysed the accuracy of PET for residual and recurrent NPC or detected the lymph node and distant metastases [5356]. As far as our information goes, our meta-analysis is the first to assess the prognostic values of 18 F-FDG PET/CT parameters in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 of these literature were about NPC and they all analysed the accuracy of PET for residual and recurrent NPC or detected the lymph node and distant metastases [5356]. As far as our information goes, our meta-analysis is the first to assess the prognostic values of 18 F-FDG PET/CT parameters in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-Fluoro-deoxy-glucose positron emission tomography ( 18 F-FDG-PET) has been applied in assessing the treatment response for NPC [4] and other tumors such as head and neck squamous cell carcinoma (HNSCC), [5,6] rectal cancer, [7] and breast cancer. [8] However, the complex anatomy of nasopharynx, low spatial resolution, and treatment-induced inflammation may decrease the accuracy of 18 F-FDG-PET.…”
Section: Introductionmentioning
confidence: 99%
“…Although this could be partially explained by the reduction of false positive caused by inflammation, higher prevalence of residual disease after 3‐4 months might also contribute to the higher PPV. PPV of posttherapy PET/CT has been considered suboptimal in HNSCC, and delayed scanning proved little difference …”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis suggests that PET/CT enjoyed higher specificity and diagnostic odds ratio in the diagnosis of residual/recurrent NPC compared with MRI, but heterogeneity exists in test characteristics (threshold, comparator, reference standard, timing, etc). 3,4 Given the potential benefits, Hopkins criteria were introduced into the posttreatment assessment of HSNCC to standardize the interpretation. 5 Subsequent studies showed a reduction of equivocal results and improved consistency using this scoring system.…”
Section: Introductionmentioning
confidence: 99%